Are newly launched pharmacotherapies efficacious in treating idiopathic pulmonary fibrosis? Or is there still more work to be done?. (13th October 2017) - Inchingolo, Riccardo; Condoluci, Carola; Smargiassi, Andrea; Mastrobattista, Annelisa; Boccabella, Cristina; Comes, Alessia; Golfi, Nicoletta; Richeldi, Luca
ABSTRACT: Introduction : Idiopathic pulmonary fibrosis (IPF) is a challenging and multifactorial disease that has been thought for some time to lack effective treatments. The approval of two drugs, nintedanib and pirfenidone, has heralded a new era in its management. Areas covered : Currently, there is a growing interest on therapeutic strategies. Many studies have been designed and performed, although few of them turned out to be successful. Nowadays, nintedanib and pirfenidone are considered disease modifying drugs, recommended treatments by current evidence-based guidelines. A combined approach with more than one drug could be an effective strategy in IPF. However, data on combination therapy of the two approved drugs are still scarce, and ongoing trials are evaluating pharmacodynamic interactions and safety. The approved disease modifying drugs are also being assessed in combination with new molecules, showing promising results in preclinical models. Expert opinion : A deeper understanding of pathogenesis and key molecular mechanisms driving disease inception and progression will be key to identify novel agents to be tested both pre-clinically and clinically, possibly in combination with approved treatments. Looking at the near future, it is likely that clinical trials will adopt a phenotype-specific and pathway-specific approach, thus leading towards a personalized approach to IPF management.